2004
DOI: 10.1111/j.1365-294x.2004.02344.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast DNA variation in the Quercus affinisQ. laurina complex in Mexico: geographical structure and associations with nuclear and morphological variation

Abstract: The geographical distribution of chloroplast DNA (cpDNA) variation in 39 populations of two hybridizing Mexican red oaks, Quercus affinis and Q. laurina, was investigated using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Six haplotypes were identified. Of these, two (H1 and H4), separated by four mutations, had high frequencies (58 and 23% of the individuals, respectively) and were present across the whole geographical range of both species, often co occurring in the same pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 45 publications
(93 reference statements)
2
28
0
4
Order By: Relevance
“…Three stands (The Netherlands 98, Great Britain and Denmark) exhibited a global percentage of hybrid acorns of ≥ 30%. Widespread evidence of hybridisation exists in oak species, highly variable in direction and intensities (for recent examples see [59], [5], [7], [10], [6], [60]). Nevertheless, local hybridisation rates are certainly affected by a variety of factors such as tree density, flowering time, micro-environmental selection, species assignment, sampling strategy and the relative spatial arrangement of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Three stands (The Netherlands 98, Great Britain and Denmark) exhibited a global percentage of hybrid acorns of ≥ 30%. Widespread evidence of hybridisation exists in oak species, highly variable in direction and intensities (for recent examples see [59], [5], [7], [10], [6], [60]). Nevertheless, local hybridisation rates are certainly affected by a variety of factors such as tree density, flowering time, micro-environmental selection, species assignment, sampling strategy and the relative spatial arrangement of the species.…”
Section: Discussionmentioning
confidence: 99%
“…These zones are also suggested by the Q. crassifolia × Q. crassipes complex (TovarSánchez & Oyama 2004) in which three gall morphotypes were exclusively associated with the hybrid individuals found there (Tovar-Sánchez & Oyama 2006). However, this pattern cannot be generalized, since in another hybrid complex formed by Q. affinis × Q. laurina (González-Rodríguez et al 2004, only one gall morphotype was found in each of the species in this study (see Table 1). …”
Section: Gall Diversity On Mexican Oaksmentioning
confidence: 41%
“…However, there is a broad area of overlap between P. strobiformis and P. ayacahuite mainly in the TMVB, an area that has already been identified as a contact zone for other temperate species (Fig. 2b; [48]). However, is important not to forget that ENMs are a simplification of the potential niche of a species and therefore, an over-prediction.…”
Section: Discussionmentioning
confidence: 98%